Protamine 2 deficiency results in Septin 12 abnormalities - Sanovec, Ondrej; Frolikova, Michaela; Kraus, Veronika; Vondrakova, Jana; Qasemi, Maryam; Spevakova, Daniela; Simonik, Ondrej; Moritz, Lindsay; Caswell, Drew Lewis; Liska, Frantisek; Ded, Lukas; Cerny, Jiri; et al. (Frontiers in Cell and Developmental Biology, 2024)
There is a well-established link between abnormal sperm chromatin states and poor motility, however, how these two processes are interdependent is unknown. Here, we identified a possible mechanistic insight by showing that Protamine 2, a nuclear DNA packaging protein in sperm, directly interacts with cytoskeletal protein Septin 12, which is associated with sperm motility. Septin 12 has several isoforms, and we show, that in the Prm2 -/-sperm, the short one (Mw 36 kDa) is mis-localized, while two long isoforms (Mw 40 and 41 kDa) are unexpectedly lost in Prm2 -/-sperm chromatin-bound protein fractions. Septin 12 coimmunoprecipitated with Protamine 2 in the testicular cell lysate of WT mice and with Lamin B1/2/3 in cotransfected HEK cells despite we did not observe changes in Lamin B2/B3 proteins or SUN4 expression in Prm2 - /-testes. Furthermore, the Prm2 -/-sperm have on average a smaller sperm nucleus and aberrant acrosome biogenesis. In humans, patients with low sperm motility (asthenozoospermia) have imbalanced histoneprotamine 1/2 ratio, modified levels of cytoskeletal proteins and we detected retained Septin 12 isoforms (Mw 40 and 41 kDa) in the sperm membrane, chromatin-bound and tubulin/mitochondria protein fractions,. In conclusion, our findings present potential interaction between Septin 12 and Protamine 2 or Lamin B2/3 and describe a new connection between their expression and localization, contributing likely to low sperm motility and morphological abnormalities.